2004
DOI: 10.1242/jcs.01342
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA synthetase complexes: beyond translation

Abstract: Although aminoacyl-tRNA synthetases (ARSs) are housekeeping enzymes essential for protein synthesis, they can play non-catalytic roles in diverse biological processes. Some ARSs are capable of forming complexes with each other and additional proteins. This characteristic is most pronounced in mammals, which produce a macromolecular complex comprising nine different ARSs and three additional factors: p43, p38 and p18. We have been aware of the existence of this complex for a long time, but its structure and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(211 citation statements)
references
References 114 publications
3
199
0
3
Order By: Relevance
“…The complex consists of nine different ARSs and three AIMPs. Among these components, GST homology domains are found in the N-terminal appendices of two ARSs (MRS and glutamylprolyl-tRNA synthetase) and two AIMPs (AIMP2 and AIMP3) (35). Because these domains are detected only in these complex-forming ARSs and AIMPs and in the N-terminal appendix of valyl-tRNA synthetase that also forms a complex with the elongation factor (36), they are thought to be critical for the assembly of protein complexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The complex consists of nine different ARSs and three AIMPs. Among these components, GST homology domains are found in the N-terminal appendices of two ARSs (MRS and glutamylprolyl-tRNA synthetase) and two AIMPs (AIMP2 and AIMP3) (35). Because these domains are detected only in these complex-forming ARSs and AIMPs and in the N-terminal appendix of valyl-tRNA synthetase that also forms a complex with the elongation factor (36), they are thought to be critical for the assembly of protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Although transfection of wild-type AIMP3 enhanced the luciferase activity about 4-fold, all mutants except for the Thr 35 / Ser 40 mutant demonstrated less luciferase activity than the wild type (Fig. 5D).…”
Section: Journal Of Biological Chemistry 14037mentioning
confidence: 95%
See 2 more Smart Citations
“…Mouse studies have shown neuronal expression of AIMP1 in a variety of regions of the central nervous system, including the ventral horn of the spinal cord and the hippocampus. 4,5 To date, two variants for the AIMP1 gene (OMIM *603605) have been reported and these are associated with severe neurodegenerative disorder. The first alteration is a homozygous 2-bp deletion (NM_001142415.1, c.292_293delCA, p.(Gln98Valfs*30)) in exon 4 of AIMP1 that was found in six affected individuals from three related families, as well as in one single individual of another very remotely related consanguineous family of the same tribe.…”
Section: Introductionmentioning
confidence: 99%